1995
DOI: 10.1007/bf01271551
|View full text |Cite
|
Sign up to set email alerts
|

Crucial role of the accumbens nucleus in the neurotransmitter interactions regulating motor control in mice

Abstract: Previous work, based on systemic drug administration, has shown that neurotransmitter interactions between dopaminergic, adrenergic, glutamatergic and cholinergic systems are involved in locomotor control in mice. In an attempt to identify the target sites in the brain of these interactions, we have started a series of experiments, where the drugs are administered intracerebrally in mice. The locomotor threshold doses of the competitive NMDA antagonist AP-5 and the noncompetitive NMDA antagonist MK-801 were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 53 publications
(64 reference statements)
1
18
1
Order By: Relevance
“…It has been reported that MK-801 increases DA release in the locus coeruleus, but decreases uptake of norepinephrine in the locus coeruleus and that of 5-HT in the dorsal raphe nucleus. However, different results had been reported for effect of MK-801 on DA release in the ACC: no effect (36,37), increase (26,32,38,39) and even decrease (40). Our results indicate that MK-801at 0.1 mg /kg did not increase DA level in the cACC.…”
Section: Discussioncontrasting
confidence: 35%
See 2 more Smart Citations
“…It has been reported that MK-801 increases DA release in the locus coeruleus, but decreases uptake of norepinephrine in the locus coeruleus and that of 5-HT in the dorsal raphe nucleus. However, different results had been reported for effect of MK-801 on DA release in the ACC: no effect (36,37), increase (26,32,38,39) and even decrease (40). Our results indicate that MK-801at 0.1 mg /kg did not increase DA level in the cACC.…”
Section: Discussioncontrasting
confidence: 35%
“…A subthreshold i.p. dose of MK-801 produces locomotor stimulation after alpha-methyl-noradrenaline injection into the ACC but not into the dorsal striatum, prefrontal cortex or thalamus (38). MK-801-hyperlocomotion is accompanied by increased DA release in the cACC, but not in the ventral pallidum (46).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Even more, the comparison of the two temporal profiles suggests that histaminergic neurons are involved in a compensatory manner in the modulation of this response, inasmuch as t-MeHA levels were also increased in the nucleus accumbens, known to be associated with the regulation of locomotor function (Svensson et al, 1995). Consistent with this proposal, enhanced release of endogenous histamine attenuates stimulant-induced locomotor activity (Itoh et al, 1984;Clapham and Kilpatrick, 1994;Ito et al, 1997), and ciproxifan, an H 3 receptor inverse agonist known to enhance histamine neuron activity (Morisset et al, 2000a), strongly decrease methamphetamine-induced hyperlocomotion.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, there seems to be both direct and indirect striatothalamic pathways, and accordingly both positive and negative cortico-striato-thalamo-cortical feedback circuits (see Svensson et al, 1995).…”
Section: Introductionmentioning
confidence: 98%